The creation of junior schoolchildren’s interest in the experimental study of physical phenomena using the elements of the technology of problem-based - F M, Sabirova; A V, Deryagin (International Journal of Engineering and Technology, 2018)
The goal of the paper is to define the place and role of the technology of problem-based learning in demonstrating physical phenomena and processes to junior schoolchildren within a framework of the Child University and InteLSummer projects of Elabuga Institute of Kazan Federal University for higher interest in learning physics – a science about nature. The method is the technology of problem-based learning. Children face a certain problem, which is a cognitive task, and students (themselves or assisted by a teacher) investigate the ways and methods to solve it. We can use the elements of problem-based technology (creation of a problem, joint scientific learning, and primary reinforcement of the obtained knowledge) in teaching junior schoolchildren. Results: we considered the ways of creating particular problem situations with both a teacher and, most importantly, children participating in their solution on the example of a cycle of laboratory and practical classes devoted to electrical and magnetic phenomena. In the end, the experience of applying the technology of problem-based learning has shown that children’s participation in looking for the ways to solve a learning problem supports a cognitive interest of junior schoolchildren in the study of physical phenomena. The participation of pedagogical university students - future teachers - in the Child University and Intel Summer projects is a perspective form of a practice-oriented approach to future professional activity.
Keywords: Interest in Learning; Physics; Junior Schoolchild; Motivation; Technology; Problem-Based Learning; Experiment; Electricity; Magnet; Magnetism; Experimental Check; Physical Properties.